Un mal intolérable : revendiquer des services en santé mentale pour la jeunesse franco-ontarienne avant la crise de l’Hôpital Montfort - Arsenault, Mathieu; Martel, Marcel (Minorités linguistiques et société, 2018)
Dans les années 1970, la question de l’accès aux soins de santé mentale en français pour la minorité francophone émerge dans l’espace ontarien, notamment grâce aux pressions de l’ACFO et au rapport Dubois sur les services de santé en français. Dès lors, la question des soins de santé mentale pour la jeunesse constitue un aspect crucial de la bataille pour l’accès à des soins de santé en français. Symbole par excellence du sujet minoritaire, le jeune Franco-Ontarien s’impose comme catalyseur du discours de la classe politique, des groupes d’intérêts et des parents qui écrivent au ministre provincial de la Santé pour revendiquer des services de santé mentale en français et pour réclamer la mise en place d’une politique-cadre en matière de santé. Mots-clés : santé mentale, jeunesse, Franco-Ontarien, services en français, correspondance

Soins à domicile en français. Rapport final - Atlantic Evaluation Group Inc (2013)

L’offre active et l’accessibilité des services sociaux et de santé chez les personnes atteintes de démence en contexte francophone minoritaire - Bélair, Josée (Université d'Ottawa, 2019)
À l’heure actuelle, les besoins de soins de santé augmentent en réponse à la démographie vieillissante (Organisation mondiale de la santé, 2018). Pourtant, la difficulté d’accès aux services sociaux et de santé chez les usagers en situation minoritaire est une réalité présentée à l’aide de la littérature scientifique. En ce qui a trait aux populations minoritaires de la ville d’Ottawa, les études antérieures permettent de démontrer les obstacles touchant plus particulièrement les personnes francophones dans l’accessibilité des services sociaux et de santé (Kubina et collab., 2018). Dans le contexte de cette étude qualitative, le diagnostic de démence est pris en compte en tant que facteur explicatif de la difficulté accrue vécue chez les aînés francophones dans le recours aux services sociaux et de santé (Carbonneau et Drolet, 2014b). Un total de cinq proches aidants de la ville d’Ottawa a été recruté dans le but d’alimenter les objectifs de la recherche, c’est-à-dire : 1) d’identifier les barrières linguistiques dans la trajectoire des services sociaux et de santé ; 2) d’identifier l’influence des structures du Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire (CALA) (Savard et collab., 2017) (Voir figure 1) dans l’accès aux services sociaux et de santé chez la population à l’étude. Quoique la majorité des participants à la recherche aient exprimé leur satisfaction par rapport aux services en français reçus pour leur proche atteint d’une démence, certaines barrières linguistiques telles que le manque de continuité dans les services en français ont été identifiées ainsi que le manque d’information quant à la disponibilité des services dans la communauté. De plus, la majorité des participants à la recherche ont pu identifier au moins un moment où les services à leur disponibilité étaient strictement en anglais. Bref, parmi les cinq proches aidants interviewés, quatre ont mentionné la nécessité de lutter pour l’obtention des services en français.

Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Points saillants sur la santé mentale des jeunes franco-canadiens d’est en ouest du pays : le témoignage de nos assistantes de recherche - Benoit, Monique; Beaton, Ann. M. (Minorités linguistiques et société, 2018)

Citoyens de deuxième classe ? Perceptions de la santé et du système de soins chez les francophones du nord-est de l’Ontario - Bernier, Christiane (Francophonies d'Amérique, 2009)
Cette enquête a pour objectif d’analyser les représentations que les francophones vivant en situation minoritaire ont de leur santé et de celle de leur communauté, de même que leurs perceptions des systèmes de soins auxquels ils ont accès, particulièrement lorsqu’ils vivent dans des régions rurales ou éloignées. De type qualitatif, l’enquête a été réalisée dans le nord-est de l’Ontario auprès de 32 francophones provenant de dix villes différentes. Les résultats montrent que le mépris de la langue minoritaire, le manque de services et de considération pour les francophones ainsi que le faible intérêt accordé par le gouvernement aux usagers des régions éloignées sont les pivots autour desquels se construisent l’insécurité et les désillusions par rapport au système de santé de la province.

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)
fs-ref-orig: Bouchard, L., Batal, M., Imbeault, P., Gagnon-Arpin, I., Makvandi, E., & Sedigh, G. (2012). The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS). Réseau de recherche appliquée sur la santé des francophones de l'Ontario. fs-code-orig: Bouchard-2012d

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

Impact de la situation linguistique minoritaire sur les soins de santé pour des personnes âgées francophones de l'Ontario souffrant de maladies chroniques : une étude qualitative exploratoire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Consortium national de formation en santé, 2010)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)
fs-ref-orig: Bouchard, L., Gagnon-Arpin, I. et Makvandi, E. (2012). Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est. Réseau de recherche appliquée sur la santé des francophones de l’Ontario. fs-code-orig: Bouchard-2012e

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Instantané de recherche : l’avantage surprenant des jeunes francophones touchées par la dépression - CAMH-Evidence Exchange Network (2020)
Cet Instantané de recherche résume l’article intitulé « Les enjeux intersectionnels de la demande de services de santé mentale au Canada : La situation des jeunes femmes dépressives francophones », publié dans la Revue canadienne de service social en 2018.

La trajectoire des services sociaux et de santé d’aînés atteints d’une démence vivant en contexte francophone minoritaire : un engagement de multiples piliers durant une navigation complexe - Carbonneau, Corine; Drolet, Marie (Reflets, 2014)

Dans la langue officielle de son choix : la loi canadienne sur les langues officielles et la notion de « choix » en matière de services publics - Charbonneau, François (Lien social et Politiques, 2011)
L’article s’intéresse à la notion de choix en matière de services publics à la lumière de l’expérience de la notion de « langue de son choix » incluse dans les diverses législations canadiennes depuis plus de quarante ans, c’est-à-dire depuis l’adoption de la Loi sur les langues officielles au Canada. Cet exemple montre bien comment le choix en matière de services publics peut avoir des conséquences délétères non intentionnelles pour les populations les plus vulnérables, dans ce cas-ci, les francophones vivant en situation minoritaire.

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Portrait des minorités de langue officielle au Canada : les francophones de l'Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Francophones in Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistics Canada, 2010)

English-language Health and Social Services Access in Québec. Comparison 2019-2023 - CROP (Community Health & Social Services Network, 2023)

L’accès en anglais aux services de santé et aux services sociaux au Québec. Version française du rapport comparatif 2023-2019 - CROP (Community Health & Social Services Network, 2024)

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Disponibilité et accessibilité des services de santé en français au Manitoba. Rapport final - de Moissac, Danielle; de Rocquigny, Janelle; Roch-Gagné, Margaux; Giasson, Florette (Université de Saint-Boniface et Institut franco-ontarien de l’Université Laurentienne, 2011)

Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains - de Moissac, Danielle; Giasson, Florette; Roch-Gagné, Margaux (Minorités linguistiques et société / Linguistic Minorities and Society, 2015)
Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En moyenne, 50 % des répondants disent demander des services en français, mais seulement 25 % affirment les recevoir. La pénurie de professionnels pouvant offrir des services en français est considérée comme la barrière principale à l’accès. L’offre active est essentielle et facilite la prestation des services dans la langue de choix de la clientèle. Mots-clés : accessibilité, santé, services sociaux, Manitoba, minorité francophone

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Health status of minority Francophone seniors in Manitoba and access to services in french: Potential for social isolation - de Moissac, Danielle; Roch-Gagné, Margaux; Ba, Halimatou; Gueye, Ndèye Rokhaya; Ethier, Sophie (Human Development, Disability, and Social Change, 2016)
Francophone seniors in Manitoba represent a growing and vulnerable population, with poorer health outcomes and limited access to health and social services in the official minority language. To avoid isolation, support services are required, as chronic diseases and reduced mobility have a direct impact on both physical and social needs. The purpose of this study is to examine the current health status of seniors in the Francophone minority population of Manitoba and their access to health and social services in French. Demographic, social and health profiles were obtained for Francophone and non-Francophone Home Care clients in Winnipeg. Although diagnosed with similar health conditions as non-Francophones, Francophone seniors are less likely to be assessed with reduced cognitive performance and conditions making mood and behaviour unstable, such as dementia other than Alzheimer’s. Gaps in bilingual health services were identified for pharmacy, audiology and occupational therapy services, meal and transportation systems as well as support services for informal caregivers. Housing options with in-house support services provided in French are available and additionally provide opportunities for seniors to socialize with other Francophones. For the elderly living in singlehome units and their caregivers, support services provided in the official minority language are needed. Keywords: seniors, health, Francophone minority, home care

Besoins et services en français en matière de sexopérinatalité chez les couples parentaux franco-ontariens - de Pierrepont, Catherine; Polomeno, Viola; Bouchard, Louise; Reissing, Elke (Minorités linguistiques et société, 2017)
Cet article dévoile un portrait des besoins et des services en français en matière de sexopérinatalité perçus par 67 couples parentaux francophones en situation linguistique minoritaire d’Ottawa et de l’Est de l’Ontario. Les couples ont des besoins d’informations et de soutien ; pour eux, il est important d’aborder la sexualité pendant la période périnatale. Toutefois, le sujet est peu discuté avec les professionnels de la santé, et très peu de services sexopérinataux en français sont offerts, même s’ils sont souhaités par ces couples. Les discussions sur la sexualité qui se déroulent majoritairement en anglais constituent un obstacle supplémentaire pour une majorité des couples. Mots-clés : sexualité périnatale, couples parentaux, périnatalité, francophones en situation linguistique minoritaire, services de santé en français

Utilisation des services gouvernementaux de langue française. Une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités linguistiques, 2009)

Utilisation des services gouvernementaux de langue française : une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français : sommaire - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités liguistiques, 2010)

Accès aux services en santé dans la langue officielle de leur choix par les minorités francophones hors Québec. Analyse de données secondaires - Diaz Pinsent Mercier Research Inc (Consortium national de formation en santé, 2021)

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Agir pour avoir accès à des services sociaux et de santé en français. Des francophones en situation minoritaire nous enseignent quoi faire! - Drolet, Marie; Arcand, Isabelle; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée (Revue canadienne de service social, 2015)
Même si les droits des francophones de l’Ontario sont garantis par la Loi de 1986 sur les services en français, l’accès à des services sociaux et de santé en français dans cette province s’avère complexe en raison d’importantes barrières à recevoir de tels services sur un continuum. Nous avons exploré à l’aide d’entrevues qualitatives les points de vue de 40 parents et proches aidants francophones qui vivent en contexte bilingue dans la région d’Ottawa et dont l’enfant ou l’aîné pour lequel ils ont une responsabilité d’aidant utilise des services sociaux et de santé en français. Ces francophones s’avèrent des acteurs au sein de leur trajectoire de services, adoptant cinq stratégies pour accéder à de tels services. De plus, le sentiment de confort et la relation de confiance que procure l’usage du français tout au long de l’intervention, ainsi que le soutien des professionnels francophones ont facilité leur démarche. Il n’en demeure pas moins que l’offre de services en français ne doit pas devenir la responsabilité d’individus ou d’une minorité. Mots-clés : Francophonie en situation minoritaire, accès à des services sociaux, minorité linguistique, barrières aux services, offre active de services en français, entrevues qualitatives

L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.
Chapitre 6

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Comprendre l’expérience des femmes âgées en matière de l’accessibilité aux services sociaux et de santé en contexte francophone minoritaire [mémoire de maîtrise, Université d'Ottawa] - Dubuc, Vanessa (Université d'Ottawa, 2019)
Au Canada, les francophones en contexte minoritaire demeurent contraints au niveau de l’accès aux services sociaux et de santé en français en raison de barrières linguistiques. De plus, les femmes âgées en contexte francophone minoritaire sont sujettes aux inégalités vécues par les femmes âgées de façon générale, mais subissent également de la discrimination liée à leur statut de minorité. La présente recherche s’intéresse à l’expérience des femmes âgées en contexte francophone minoritaire en matière d’accessibilité aux services sociaux et de santé. De manière plus précise, cette recherche a pour but : 1) d’identifier les facilitateurs et les défis rencontrés par ces femmes ; 2) de comprendre la manière dont ces facilitateurs et ces défis ont des effets sur les différentes sphères de leur vie ; 3) examiner l’effet des structures institutionnelles et organisationnelles quant à l’accessibilité aux services sociaux et de santé de celles-ci. Afin de recueillir nos données, des entrevues semi-structurées ont été effectuées auprès de quatre participantes. L’analyse thématique des données, suivant un cadre théorique féministe intersectionnel, permet de mettre en évidence les éléments suivants selon les expériences des participantes : 1) l’accès aux services sociaux et de santé en contexte francophone minoritaire ; 2) la question du genre ; et 3) les réalités structurelles. Concrètement, les résultats indiquent que les participantes ont de la difficulté à accéder à des services sociaux et de santé dans leur langue, mais que le fait de s’identifier comme une femme ne semble pas jouer un rôle déterminant dans leur accès aux services en français. À la lumière des résultats, des recommandations sont proposées afin de mieux répondre aux besoins des groupes en situation linguistique minoritaire. Mots clés : francophone minoritaire, femme âgée, accès aux services sociaux et de santé, féminisme intersectionnel

La perception des aînés francophones en situation minoritaire face aux défis et aux enjeux liés au maintien à domicile en milieu urbain néo-brunswickois - Dupuis-Blanchard, Suzanne M.; Simard, Majella; Gould, Odette N.; Villalon, Lita (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Explorer les besoins et le degré de satisfaction des aînés francophones en situation sociolinguistique minoritaire au sein d’une communauté urbaine concernant la problématique du maintien à domicile. Méthode Une étude de cas de type ethnographique fut réalisée dans une communauté urbaine du Nouveau-Brunswick entre octobre 2010 et juin 2011. Nous avons effectué des entrevues individuelles avec les responsables d’organismes communautaires (n=9) et des groupes de discussion avec des personnes âgées francophones demeurant en contexte sociolinguistique minoritaire (n=19). Résultats Les aînés francophones rencontrés nous ont exprimé leur volonté de vieillir chez eux. En revanche, le manque de services et de soutien manifesté par les aînés francophones représente un obstacle au maintien à domicile. En dépit de ces lacunes, les responsables d’organismes communautaires ne prévoient pas modifier leurs services en vue de favoriser l’amélioration de la qualité de vie des aînés. Conclusion Le maintien à domicile pour les aînés francophones en milieu minoritaire requiert des actions concertées issues de la famille, de la communauté et de l’État. Selon la Charte d’Ottawa, le logement constitue une condition préalable à la santé. De plus, le logement et les réseaux sociaux sont des déterminants de la santé. Par conséquent, l’élaboration et la mise en œuvre d’une politique publique à destination des personnes âgées et, de surcroît, en situation minoritaire nous apparaissent un enjeu fondamental dans un contexte de vieillissement démographique.

Strategies for aging in place: The experience of language-minority seniors with loss of independence - Dupuis-Blanchard, Suzanne; Gould, Odette N.; Gibbons, Caroline; Simard, Majella; Éthier, Sophie; Villalon, Lita (Global Qualitative Nursing Research, 2015)
For healthy and independent older adults, aging in place can be seen as identical to any other adult living at home. Little is known about how frail seniors, particularly those who speak a minority language, manage the challenges of aging in place. The present qualitative descriptive study explores the strategies that Canadian French-speaking seniors have put in place to counter their loss of independence and promote their ability to stay in their home. Semistructured individual interviews were conducted with 39 older adults and transcribed, followed by content analysis to identify common themes related to study objectives. Six themes emerged in response to strategies described for aging in place. Findings reveal the limited extent to which language issues were perceived as a barrier by participants. In conclusion, the results of this study provide us with fruitful insights to guide community nursing practice, future research, and public policy.

Perceptions of healthy aging among Francophone older adults living in Edmonton, Alberta [master's thesis, University of Alberta] - Esso, Christelle. M.-C. (University of Alberta, 2013)
fs-ref-orig: Esso, C. M.-C. (2013). Perceptions of healthy aging among Francophone older adults living in Edmonton, Alberta [master's thesis, University of Alberta]. Education & Research Archive. https://doi.org/10.7939/R3R785X66 fs-code-orig: Esso-2013

« I don’t think that’s the way healthcare for an 85 and an 88-year-old should be done. » L’accès aux services de santé et aux services sociaux des aînés anglophones vivant hors Montréal : état de la situation [thèse de maîtrise, Université de Sherbrooke] - Ethier, Alexandra (Université de Sherbrooke, 2020)
Les aînés anglophones du Québec hors Montréal ont un accès variable aux services de santé et services sociaux (SSSS). C’est pourquoi notre recherche explore l’accès aux SSSS pour les aînés anglophones vivant hors Montréal. Spécifiquement, nous décrivons les facteurs (facilitateurs et barrières) influençant l’accès aux SSSS. Ainsi, nous avons conduit une recherche qualitative de type étude de cas unique imbriquée. Nous avons collecté les données à l’aide d’entretiens semi-dirigés audio-enregistrés, d’un questionnaire sociodémographique et d’un journal de bord. Nous avons transcrit, puis analysé thématiquement les entretiens et avons analysé les données sociodémographiques par statistiques descriptives. Les 10 aînés rencontrés nous ont permis d’identifier 11 facteurs divisés en 6 facilitateurs et 8 barrières influençant l’accès aux SSSS. Les plus signifiants sont la concordance (facilitateur) ou la non-concordance (barrière) de la langue de l’aîné avec le travailleur des SSSS, où la nonconcordance mène à des consentements aux interventions non valides. Également, le facteur présence minoritaire, c’est-à-dire la concentration de la population anglophone, affecte les opportunités sociales des aînés. Ce facteur est un facilitateur lorsque fort et une barrière, lorsque faible. Enfin, des SSSS peu « amis » des aînés anglophones, définis comme un système de SSSS complexe à naviguer lorsque la langue des aînés et leurs caractéristiques personnelles ne sont pas prises en considération, constituent également une barrière. Les résultats de cette recherche informent sur les actions à poser pour faciliter l’accès aux SSSS de ces aînés anglophones et suggèrent des améliorations bénéfiques pour l’ensemble de la population.

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 5 - Description des expériences de trajectoires individuelles de soins de santé en français pour les aînés | Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 5 - Description of experiences of seniors' individual trajectories in French-language health care - Éthier, Sophie; Ba, Halimatou; Belzile, Louise; Gagné, Maryanne; Roch-Gagné, Margaux (Conseil communauté en santé du Manitoba et Université de Saint-Boniface, 2012)

Seeking social services on the Gaspé coast: A narrative analysis of Anglophones’ experiences of access and care [master's thesis, University of Victoria] - Finlayson, S. (University of Victoria, 2017)
This research addresses the concern that Anglophone populations in the predominantly French speaking Gaspé region of eastern Québec are experiencing high rates of social problems such as poverty and unemployment. Anglophones in this region, as in other rural regions of Québec, have identified facing difficulties related to access to social services, an aspect which further complicates existing social problems. Using a narrative methodology and post structural, feminist and intersectional lenses, this research explores the experiences of English speaking service users in accessing and engaging with social services on the Gaspé coast. This study also explores the boundaries and reproduction of linguistic categories and identity and offers insight into resisting dominant discourses pertaining to linguistic difference in Québec, specifically within the context of social services. The results of this research demonstrate that service users’ experiences were characterised by disproportionately negative effects in regards to service access and delivery such as intensified logistical problems and social work practice related weaknesses. The research also concludes that experiences involved multiple, intersecting problems, which were irreducible to the singular dimension of language. The intersections of language and race, language and class, and language and ability were raised as critical concerns in terms of access to social services on the Gaspé coast. Finally, the encounters between Anglophones and Francophones in the context of health and social services in the region were found to be entangled and inseparable from the historical and ongoing political struggles over language on this territory.

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

L’accès aux services de santé en français et leur utilisation en contexte francophone minoritaire. Rapport final - Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

Les enjeux intersectionnels de la demande de services de santé mentale au Canada : la situation de jeunes femmes dépressives francophones - Gaborean, Florina; Negura, Lilian; Moreau, Nicolas (Revue canadienne de service social, 2018)
Dans cet article, nous présentons, selon le cadre théorique féministe intersectionnel, une étude visant à mieux comprendre les dynamiques identitaires qui influencent la demande de services de santé mentale des jeunes femmes francophones vivant en situation minoritaire ainsi que les effets croisés de celles-ci sur les facteurs déclencheurs de la dépression, la perception des symptômes et le parcours thérapeutique. Notre analyse révèle que l’imbrication de plusieurs catégories d’inégalité complexifie l’accès aux services de santé mentale des jeunes femmes dépressives en situation minoritaire tout en favorisant l’émergence de stratégies de lutte et de résistance. Le croisement des catégories identitaires de genre, d’âge et de langue parlée produit des effets compensatoires sur la demande de services de santé mentale. Alors que l’image sociale positive de la jeunesse les fait hésiter dans la demande de services, celle liée à l’identité féminine légitime, la dépression et les faiblesses qui pourraient en découler. Les femmes mettent en oeuvre des stratégies pour pallier les inégalités d’accès aux services de santé mentale en français et trouver les services qu’elles considèrent appropriés pour leur problème spécifique. Au lieu de favoriser la discrimination ou la marginalisation, cette imbrication d’appartenances identitaires multiples permet le renforcement du pouvoir d’agir des jeunes femmes francophones. Mots-clés : Dépression, femmes, jeunes, intersectionnalité, services de santé mentale, francophonie minoritaire

Les services de santé en français en Ontario: Offre - demande - utilisation - Gagnon-Arpin, Isabelle; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2011)

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Mobilisation et engagement des aînés pour une communauté en santé - Haché, Linda; Chiasson, Chiasson S. (Gouvernance, santé et minorités francophones : stratégies et nouvelles pratiques de gestion au Canada, 2007)

Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

Perceived importance of native language use in service encounters - Holmqvist, Jonas; Van Vaerenbergh, Yves (The Service Industries Journal, 2013)
Despite the importance of interactions in services, the role language plays in services is an under-researched field. This paper outlines for which services language is especially important. Consistent across studies in three countries (Belgium, Canada and Finland), the findings suggest that bilingual consumers find it particularly important to be served in their native language in high-involvement services. Moreover, for high-involvement services, all consumers find it important to be served in their native language. For low-involvement services, elderly consumers are less willing to switch language than young consumers. The importance of native language use did not differ between males and females.

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Pour une communauté francophone en bonne santé : une étude de cas dans une communauté francophone en situation minoritaire - Kennedy, Evelyn; McIsaac, Corrine (Revue de l’Université de Moncton, 2008)
C’est dans la communauté rurale de Chéticamp que le programme sur l’initiative des soins de santé primaires pour les communautés francophones (Francophone Primary Health Initiative Program) a été établi. Environ 50 % des initiatives proposées ciblent les personnes âgées, notamment l’amélioration de la santé cardiovasculaire, l’augmentation du niveau d’activité physique et de l’information reliée aux médicaments. Tous les projets ciblent un certain nombre d’habitudes de vie saines et prévoient l’accès à des services médicaux en français, en insistant sur l’importance de services offerts en français. Cette note de recherche rapporte les résultats obtenus auprès de trois groupes de discussion sur l’état de santé de cette petite communauté francophone. L’analyse qualitative présente des données obtenues pendant les cliniques concernant le bien-être des personnes âgées. Même si les personnes âgées participantes aux groupes de discussion se disent en bonne santé, les groupes de discussion donnent différentes raisons concernant l’abandon de projets d’activité physique antérieurs et apportent des suggestions pour de nouvelles démarches. Il est probable que les initiatives de promotion de la santé mettant en oeuvre des stratégies basées sur des données probantes réussissent à améliorer la santé des communautés. Il est temps pour le gouvernement de soutenir les stratégies à long terme afin de concrétiser le développement de communautés en bonne santé. Mots-clés: soins de santé primaires, communautés francophones en situation minoritaire, personnes âgées, Société Santé en français, régie régionale de la santé Cape Breton

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)
fs-ref-orig: Léger. (2020). Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final. Santé Canada. fs-code-orig: Léger-2020

Impact de la situation linguistique minoritaire sur les soins de santé pour les personnes âgées francophones de l’Ontario souffrant de maladies chroniques : partage des connaissances et rétroaction. Rapport de recherche - Lemonde, Manon; Boudreau, Françoise; Dufour, Suzanne (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Déterminants socio-économiques affectant le choix d’une maison de retraite : points de vue des résidents d’une maison francophone à Toronto [thèse de maîtrise, Université Laurentienne] - Maïna, Ali (2013)
Cette étude vise à explorer le problème de logement lié au vieillissement de la population. L’objet principal de la présente thèse est de comprendre les déterminants socioéconomiques qui influencent la décision des personnes âgées d’aller vivre en maison de retraite et leur choix d’une maison de retraite en particulier. Les données ont été collectées à l’aide d’une méthode qualitative, par l’entremise d’entrevues semi-directives. Les trente-sept personnes âgées constituant notre échantillon se sont exprimées sur leurs expériences afin de nous permettre de mieux cerner les déterminants socio-économiques affectant leur choix d’aller vivre en maison de retraite. Tous nos participants sont des résidents de la maison Héritage, une institution de Toronto. Les résultats de cette recherche nous révèlent que le choix d’aller vivre dans une maison comme l’Héritage implique des aspects qui dépassent largement les motifs purement économiques. En conséquence, les déterminants liés à la solitude, aux décès de conjoint (e), au soutien adapté, ont été très influents dans la première phase du choix d’aller vivre dans une maison de retraite. En revanche, dans le choix de l’Héritage, des déterminants liés à l’identité, comme la langue, les valeurs culturelles, ont été plus influents. Mots-clés déterminants socio-économiques, personnes âgées, maison de retraite, maison francophone (Héritage), langue, valeurs culturelles, financier

Soins de longue durée en français. Rapport final - McQuaid, Steve (The Atlantic Evaluation Group Inc, 2010)

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada - Michaud, Jacques; Forgues, Éric; Guignard Noël, Josée (Minorités linguistiques et société, 2015)
L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la population d’aînés francophones, ainsi qu’un aperçu du contexte réglementaire encadrant le fonctionnement de ces résidences permettent de définir la problématique pertinente. Des actions en vue d’améliorer la situation sont examinées. Mots-clés : espace francophone, services de santé en français, francophones en situation minoritaire, foyers de soins, résidences collectives, vieillissement de la population

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

La représentation sociale de la dépression et l’accès aux services de santé mentale des jeunes francophones canadiens en contexte minoritaire - Negura, Lilian; Moreau, Nicolas; Boutin, Émilie (Penser les liens entre santé mentale et société : les voies de la recherche en sciences sociales, 2014)

Les femmes aidantes naturelles dans les communautés francophones et acadienne du Canada. Sommaire - Ouimette, Johanne; Miron, Isabelle. N (Alliance des femmes de la francophonie canadienne, 2006)

Accès au diagnostic précoce de démence au Nouveau-Brunswick : perceptions d’usagers potentiels de services selon la langue et le milieu de vie - Pakzad, Sarah; Jbilou, Jalila; Paulin, Marie-Claire; Fontaine, Véronique; Donovan, Denise; Bélanger, Mathieu; Bourque, Paul-Émile (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Le diagnostic précoce de la démence (DPD) est crucial autant pour l’identification des causes réversibles que pour la mise en place rapide d’interventions de prévention secondaire et de prise en charge thérapeutique. Cette étude explore la perception d’aînés du Nouveau-Brunswick concernant l’accessibilité, la disponibilité et la satisfaction des services de DPD, en tenant compte de leur langue d’usage et de leur milieu de vie (urbain ou rural). Méthode Questionnaire auto-administré explorant les perceptions d’aînés francophones et anglophones de régions rurales et urbaines du Nouveau-Brunswick concernant les services de DPD. Des analyses univariées et bivariées ont été réalisées. Résultats Parmi les 157 participants âgés de 65 ans et plus ayant répondu au questionnaire et dont les données ont été analysées, 84 déclarent être principalement francophones et 72 parmi eux vivent en milieu rural. Les analyses bivariées suggèrent que les groupes linguistiques étudiés sont comparables en ce qui concerne leurs perceptions de la disponibilité, l’accès et la satisfaction des services de DPD. Toutefois, l’introduction de la dimension géographique montre des disparités intragroupes et intergroupes linguistiques, notamment en ce qui a trait à l’information relative au type de services disponibles dans la région. Conclusion Ces résultats suggèrent que les aînés vivant en milieu rural au Nouveau-Brunswick représentent un groupe particulièrement vulnérable ayant une perception d’accès limité aux services de DPD dans leur région.

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)
https://pmc.ncbi.nlm.nih.gov/articles/PMC2231483/

Immigration et santé. Où en sont les Francophones ? Une enquête sur l'état de santé des immigrants francophones en Colombie-Britannique - Poullos, Nichollos (RésoSanté Colombie-Britannique, 2018)

Le Réseau à l’écoute. Rapport à la communauté 2022-2023. - Réseau des services de santé en français de l’Est de l’Ontario (2024)
Le Réseau des services de santé en français de l’Est de l’Ontario (RSSFE ou Le Réseau) a lancé la nouvelle initiative Le Réseau à l’écoute en février 2022 auprès des membres du Réseau et de la communauté francophone de l’Est et du Sud-Est de l’Ontario. Il s’agit d’un espace privilégié pour entendre les expériences, tant positives que négatives, qu’ont les membres de la communauté francophone avec le système de santé. Ce premier rapport à la communauté sur Le Réseau à l’écoute couvre une période de 14 mois, portent sur 26 témoignages (représentent 51 expériences distinctes) reçus entre les mois de février 2022 et la fin de mars 2023.

Le Réseau à l’écoute. Rapport à la communauté 2023-2024. - Réseau des services de santé en français de l’Est de l’Ontario (2024)
Le Réseau des services de santé en français de l’Est de l’Ontario (RSSFE ou Le Réseau) a lancé l'initiative Le Réseau à l’écoute en février 2022 auprès des membres du Réseau et de la communauté francophone de l’Est et du Sud-Est de l’Ontario. Il s’agit d’un espace privilégié pour entendre les expériences, tant positives que négatives, qu’ont les membres de la communauté francophone avec le système de santé. Ce 2e rapport fait état de la collecte des données de l’année 2023-2024, au cours de laquelle Réseau à l'écoute a reçu 35 témoignages qui représentent 57 expériences uniques. En deux ans, Le Réseau à l’écoute a reçu 61 témoignages qui représentent 108 expériences uniques, dont une croissance de 35% du nombre de répondants dans la dernière année. Les expériences obtenues grâce au Réseau à l’écoute mettent en valeur la réalité de l’accès aux services de santé en français de même que les défis auxquels sont confrontés la communauté francophone lorsqu’il s’agit de recevoir des services de santé dans sa langueé

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Consultation publique sur l'accès aux services de santé en français - RésoSanté Colombie-Britannique (2016)

Consultation publique sur l'accès aux services de santé en français (infographie) - RésoSanté Colombie-Britannique (2016)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

L’expérience des francophones des soins et des services en contexte linguistique minoritaire : bilan et perspectives. - Sauvé-Schenk, Katrine; Savard, Jacinthe; Miljours, Jean-Christophe; Bouchard, Louise (Minorités linguistiques et société, 2024)
L’objectif de cet article est de présenter un état des lieux de la recherche qui porte sur l’expérience des bénéficiaires de services sociaux et de santé en contexte francophone minoritaire. On y traite des perceptions envers les services sociaux et de santé, de la demande de services en français ainsi que des expériences d’accès à des services en français, des barrières linguistiques et de la navigation dans le système de santé. On y traite aussi les perspectives qu’apportent les recherches en cours pour 1) mieux saisir les perceptions des francophones à l’égard de l’utilisation des technologies en santé afin d’améliorer leur accès aux services en français et 2) intégrer la mesure de la perception des usagers à l’évaluation continue des services en français. Mots-clés : expérience patient, minorité linguistique, francophone, système de santé, Canada

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

Enjeux et défis du vieillissement en milieu minoritaire francophone : une analyse sous l’angle des représentations sociales. Le cas de Tracadie au Nouveau-Brunswick - Simard, Majella (Minorités linguistiques et société, 2019)
Dans le but d’améliorer les conditions de vie des aînés, de nombreux acteurs sont interpellés dans la gestion du vieillissement. Cet enjeu pose un défi particulier en milieu minoritaire francophone. Le but de cet article consiste à évaluer la perception des acteurs locaux et communautaires ainsi que celle des personnes âgées en ce qui a trait aux défis liés au vieillissement. La municipalité de Tracadie, au Nouveau-Brunswick, sert de laboratoire d’analyse. Le modèle de gérontologie environnementale est le cadre théorique retenu aux fins de notre démonstration. L’approche méthodologique repose sur l’étude de cas idiographique de type exploratoire. Les résultats révèlent de nombreuses lacunes en matière de gestion du vieillissement. Ils démontrent aussi une certaine impuissance de la part des élus municipaux à intervenir en ce domaine, d’où la nécessité de mettre en place, à l’échelle de la province, une politique territoriale du vieillissement. Mots-clés : gestion du vieillissement, milieu linguistique minoritaire, Nouveau-Brunswick, perceptions des acteurs

L'influence du contexte sociolinguistique minoritaire sur le maintien à domicile des aînés en milieu rural dévitalisé : le cas d’Acadieville au Nouveau-Brunswick - Simard, Majella; Dupuis-Blanchard, Suzanne; Villalon, Lita; Gould, Odette; Ethier, Sophie; Gibbons, Caroline (La Revue canadienne du vieillissement, 2015)
New Brunswick is one of the provinces most affected by the aging of the population. Moreover, aging at home in Francophone minority communities is a major challenge in rural areas. The goal of this paper is to identify the main advantages and disadvantages of aging at home and to expose organizational strategies deployed by seniors and their families in order to promote aging in place. The case study is the method of analysis that we have recommended. Our methodology is based on content analysis of 13 semi-structured interviews with seniors and their children. The results show that family and community support, resourcefulness and resiliency, the practice of leisure activities as well as the living environment are among the principal means used by older adults to promote aging at home.

Quand la langue fait une différence. Ce que des « bénéficiaires » pensent du système de santé mentale - St-Amand, Nérée; Vuong, Dung (Sociologie et sociétés, 2002)
Résumé En partant d'une recherche effectuée en 1993 auprès d'une soixantaine d'ex-psychiatrisés néo-brunswickois qui fréquentent maintenant des réseaux d'entraide de cette province, cet article met en évidence certains des enjeux auxquels sont confrontées les personnes " trans-institutionnalisées ". Il en ressort plusieurs différences au niveau de l'utilisation des services et du degré de satisfaction, selon l'appartenance sexuelle et la langue en particulier. De plus, cette recherche démontre que le réseau sur lequel s'appuient les ex-psychiatrisés francophones interrogés est davantage social (familles, groupe d'entraide), alors que pour la population anglophone, l'appareil institutionnel (psychiatres, institutions et cliniques) joue un rôle déterminant. Ceci soulève plusieurs questions, tant au niveau des politiques sociales que des pratiques d'intervention, en contexte minoritaire en particulier. Abstract On the basis of research carried out in 1993 on sixty or so ex-psychiatric patients who now frequent mutual aid networks in New Brunswick, this paper points out some of the issues with which these 'trans-institutionalized' persons are confronted. Differences at the level of service use and degree of satisfaction stand out, particularly in relation to gender and language. Moreover, this research shows that the network on which Francophone ex-psychiatric patients depend is more social in nature (families, mutual aid groups), whereas for the Anglophone population the institutional apparatus (psychiatrists, institutions and clinics) play a determining role. This brings up several questions, in regards to social policies as well of intervention practices, particularly in the minority context. Resumen Partiendo de una investigación efectuada en 1993 sobre unos sesenta ex-pacientes psiquiátricos de Nueva Brunswick que frecuentan actualmente la red de ayuda mutua de esta provincia, este articulo pone en evidencia algunas de las disyuntivas a las cuales se ven confrontadas las personas " trans-institucionalizadas ". Resaltan varias diferencias a nivel de la utilización de servicios y del grado de satisfacción, particularmente según la pertenencia sexual y el idioma. Además, esta investigación demuestra que la red sobre la cual se apoyan los ex-pacientes psiquiátricos francófonos interrogados, es mucho más social ( familia, grupo de ayuda mutua) mientras que para la población anglófona, el aparato institucional (psiquiatras, instituciones y clínicas) juega un rol determinante. Esto sugiere varias preguntas, tanto a nivel de las políticas sociales como de las prácticas de intervención, particularmente en un contexto minoritario.

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif

La satisfaction des patients francophones de l’Est de l’Ontario traités en réadaptation à domicile - Tardif, Charles; Dallaire, Christine (Francophonies d’Amérique, 2010)
L’accès à des services de santé en français est aujourd’hui une des revendications importantes des porte-drapeaux francophones non seulement pour assurer la santé individuelle des francophones mais aussi pour favoriser la vitalité des communautés. Cependant, certains des francophones qui font appel aux soins ou à l’appui des professionnels de la santé demandent des services en français, alors que d’autres sont satisfaits de recevoir des services en anglais. Cette étude s’inspire de l’analyse des discours développée par Michel Foucault pour examiner les discours que reproduisent les francophones qui reçoivent des soins de réadaptation à domicile, en français et/ou en anglais. Des entrevues semi-dirigées ont été effectuées avec 12 patients francophones dans l’Est de l’Ontario. Les participants de l’étude sont de façon générale satisfaits des soins reçus, mais la langue des services ne répond pas nécessairement à leurs attentes. Ce sont évidemment ceux qui ne peuvent s’exprimer en anglais, d’une part, et ceux qui s’affichent fièrement comme francophones, d’autre part, qui préfèrent recevoir des soins en français. Toutefois, ce ne sont pas que les caractéristiques linguistiques et identitaires des patients qui influencent les critères qu’ils jugent prioritaires pour évaluer les soins reçus. En effet, leur façon de concevoir leur rapport vis-à-vis le professionnel de la santé joue aussi sur l’importance qu’ils accordent à la langue des soins.

Maintien à domicile : capacité d’offre de services communautaires actuels et futurs au Nouveau-Brunswick - Thériault, Danielle; Dupuis-Blanchard, Suzanne (Service Social, 2017)
La présente étude comporte trois objectifs : 1) déterminer l’état actuel des services offerts pour le maintien à domicile; 2) explorer la nature de la planification des services futurs pour le maintien à domicile; et 3) exposer les défis reliés aux services et les moyens qui s’offrent aux organismes pour que les services répondent le plus efficacement possible aux besoins des personnes âgées francophones. De type séquentiel exploratoire mixte, cette étude a permis de recueillir des données qualitatives pour bonifier des résultats quantitatifs. Quarante-neuf gestionnaires ont répondu au questionnaire en ligne et 11 entrevues ont été réalisées. Huit thèmes communs ont été dégagés en lien avec les objectifs, thèmes qui montrent une préoccupation pour la viabilité des services communautaires en maintien à domicile. Mots-clés : personnes âgées, maintien à domicile, planification, gestion, organismes communautaires, francophones

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province. Rapport soumis au Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire) - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire). Rapport soumis au Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019b

The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). Submitted to the Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019c

Les expériences de patients francophones qui se présentent fréquemment à l'urgence pour des raison de santé mentale - Vandyk, Amanda; Lightfoot, Sophie; Levesque, Kristine; Domecq, Marie-Cécile.; Jacob, Jean Daniel (Recherche en soins infirmiers, 2022)
Introduction: Language and communication are pivotal to the safe care and management of people with mental health disorders, particularly when these patients are linguistic minorities. Objectives/method: To explore these experiences within linguistic minority populations by completing a literature review and qualitative interviews. Interviews were conducted in Ottawa, Canada, with francophone patients. The studies included in the review represented the international literature on linguistic minorities in general. Results: Overall, the experiences described in the published articles were similar to the participants' own experiences, suggesting that barriers to care exist even in settings mandated to provide services in both official languages. Discussion/conclusion: There are many barriers to the provision of mental health care services, regardless of the dominant language. However, we identified an internalized sense of responsibility felt by linguistic minority patients, who feel compelled to compensate for or fill in the language gaps of providers. Keywords: health services accessibility; language; mental health; qualitative research; rapid review.

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.